The Practice of Living Hadith of Jam'iyah Shalawat Bhenning in Preventing Radicalism of Muslim Youth in Indonesia - Nawawi, Nawawi; Mirwan, Mirwan; Zikwan, M. (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
Muslim teenagers are easy targets for radicalism groups that lead to acts of terrorism. Counteracting radicalism is not enough only through legal, police and government channels, but also needs to involve the world of recitation packaged with cultural arts. Thus, the role of living hadith, which is based on traditions that live in the community and rely on hadith, becomes important. This study aims to analyze Jam'iyah Shalawat Bhenning, as a representation of living hadith that can ward off radicalism among Muslim youth. This research uses an ethnomusicological approach. Data were collected through observation and Focus Group Discussion (FGD). The findings of this study show that Jam'iyah Shalawat Bhenning uses two main strategies in counteracting Muslim youth radicalism, namely humanistic and ethical-moral approaches with two types of input, namely positive and neutral. The positive input approach focuses on de-ideologizing radicalism, while the neutral input approach focuses on raising awareness of the dangers of radicalism. Both approaches are oriented towards fresh cultural defense. With this cultural refreshment, the radicalism movement will automatically be abandoned by society because it is considered deviating from the mainstream of religion that has taken root in society.